Analysis Of Efficiency, Effectiveness And Contribution of Regional Taxes (Reclaimation Tax And Street Lighting Tax) In Increasing Original Regional Income Of Palembang - Sari, Tri Ayu Mei; Tripermata, Lukita; Meiriasari, Vhika (International Journal of Community Service & Engagement, 2024)
The purpose of this study is to examine the effect of efficiency, effectiveness, contribution of advertisement tax and street lighting tax on Palembang City's original revenue in 2016-2020. The data used in this study is a report on the target and realization of advertisement tax revenue, street lighting tax and Palembang City's original revenue in 2016-2020. The research methodology used was descriptive quantitative analysis method. The sampling technique used was purposive sampling technique. The results prove that the efficiency of the advertisement tax and street lighting tax on the local revenue of Palembang City is very efficient. The analysis of the effectiveness of the advertisement tax on the local revenue of Palembang is quite effective and the analysis of the effectiveness of the street lighting tax is effective. The analysis of the contribution of the advertising tax is very less contributing and the analysis of the contribution of the street lighting tax is less contributing. This research is expected to be an additional literature material on the topic of local revenue.